Unlocking Innovation through Digital HRM: How Employee Development and Transformational Leadership Shape Adoption Success - Al-Shammari, Salma; Alzghoul, Amro (International Review of Management and Marketing, 2026)
Digital transformation as a shaping influence on the reshaping of HRM, above all, service-based industries like the healthcare industry, has been the focus of many articles. Digital HRM as an influence on Jordanian private hospitals' innovation acquisition, the role of employee skill development as a mediator, as well as leadership support as a situational condition, has been the center of attention here. Based on the TOE framework, as well as the RBV, the research tests the postulated relationships utilizing a structure modeling method, relying on data collected from professional persons working in hospitals. Findings indicate that, both directly as well as through the avenue of facilitating a positive effect on employee skill development, digital HRM is the prime facilitator of creativity. Healthcare organizations exhibit more capability to adopt as well as execute innovative ideas where digital HRM practice augurs opportunities for ordered mastering as well as successive professional practice. Mediating role of skill development highlights the strategic imperative of investing as a conduit between technology as well as innovation. Interesting to note is the consideration that the effect of digital HRM on creativity is insignificant altered through the influence of leadership support, indicating that, in professionalized hospital settings, other organizational forces may be more consequential. Based on the processes through which HR digitization yields innovation outcomes, the research product, hereby, contributes to the increasing body of research on digital HRM as well as on healthcare innovation. It furnishes firms as well as hospitals' menageries with valuable recommendations regarding creating innovative workforces where resources are the constraining factor.